Livestock Development : Implications for Rural Poverty, the Environment, and Global Food Security - De Haan, Cornelis; Van Veen, Tjaart Schillhorn; Brandenburg, Brian; Gauthier, Jerome; Le Gall, Francois; Mearns, Robin; Simeon, Michel (Washington, DC: World Bank, 2013)
This report provides recommendations on how to better manage ongoing changes in livestock development. First, it presents an overview of the main trends that can be expected to drive the sector over the next decades. Second it discusses the negative or positive social, environmental, and health repercussions of those trends, and the institutional, policy, and technical requirements needed to manage them. It concludes with a section on the current World Bank portfolio in the livestock sector and provides an action plan for the future. The report generally describes good practices where available and identifies strategy implications of past experience. Finally, this report summarizes the current thinking of the Animal Resources Team on the type of activities that the Bank should support. It is a direct input into the review of the Bank's rural strategy.